Psychological mechanisms of perception of author’s text of a piece of music by performers-interpreters - Yunyk, Dmytro (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2018)
Relevance of the study. Preparation of musicians-instrumentalists for stage activity at the present stage of civilization’s development requires effective methods of perception of text of a piece of music. The reliability of memorizing the author’s information and its interpretation depend on the speed and quality of perception of this musical text. Main objective of the study – to reveal the psychological mechanisms of perception of the author’s musical text by the performers-interpreters on the basis of the initial provisions of the theory of memory regarding it’s structural division by specific functional levels and the time of information preservation. Methodology of the study was based on the initial provisions of psychological memory theories about the perception of information at the sensory-perceptive and cognitive-apperceptive levels. To achieve the goal, we used methods that corresponded to the nature of the phenomena and were adequate to the tasks, namely: analysis of scientific literature; modeling the results of psychological research in the theory and methodology of musical performance; generalization of the results of experimental research in the field of musical psychology. Results and conclusions. The perception of the author’s text of the piece of music by performers-interpreters is due to the coordinated work of psychological mechanisms of their sensory register, short-term and long-term memory. Psychological mechanisms of performers-interpreters’ sensory register of performers-interpreters provide the perception of physical characteristics of the information units of the author’s musical text and a short-term hold of its “echoic footmark”. This time is enough to recognize the values of the features of these units. Psychological mechanisms of short-term memory provide parallel or sequential (if necessary, mixed) processing of “valuable” for performers-interpreters signs of information units of the author’s musical text, the transformation of “musical images” into “sound images”, their integration and coding. Psychological mechanisms of long-term memory ensure the preservation of perceived signs of information units of the author’s musical text (its transformed sound images) not in the form of sensory phenomena, but in modally independent forms (codes), which represent both for the recognition of new signs of information units, and for the implementation of the acquired information for the purpose of its enrichment, change, consolidation or implementation.